Non resolving pneumonia - A rare differential - Monisha Anandhan; R Sridhar; Prabhu; R Narasimhan (Journal of Association of Pulmonologist of Tamil Nadu, 2020)
Multiple myeloma(MM) is a malignant systemic hematological disease that arises from monoclonal plasma cells. It usually affects older patients and is characterized by the presence of monoclonal immunoproteins in the serum. They are rarely found in extramedullar^ sites. We present a case of an elderly female who came to us with Respiratory symptoms, myalgia and loose stools for 2 weeks, not responding to standard antibiotic therapy raising an alarm of non resolving pneumonia of non-infectious etiology. Further radiological and laboratory evaluations showed diffuse parenchymal infiltrate and plasmacytosis. Thus the diagnosis of Multiple myeloma was made.